ESTIMASI TOTAL AIR TERSEDIA BAGI TANAMAN PADA BERBAGAI TEKSTUR TANAH MENGGUNAKAN METODE PENGUKURAN KANDUNGAN AIR JENUH - Fitria Dwi Darmayati; Tarsicius Sutikto (Jember University Press, 2019)
ABSTRACT This research was about determine the water content using the method of saturated water content that has been carried out and were suitable in Canada, However, this method needs to be tested for tropical regions such as in Jember. This present study aimed to determine the accuracy and characteristics of the empirical equations that used in determine the water content using the method of saturated water content in several classes of soil texture. Soil samples consist of the Raung Mountains, Argopuro Mountains, and Southern Mountains zones which are expected to represent several texture classes. The empirical equation is Yfc = a + b (xfc), to determine the water content in the field capacity condition, Yw = a + b (xw), to determine the water content in a permanent wilt point condition. The empirical equation for total available water is AT = Yfc - Yw. Based on the results of the study obtained a new equation from the results regression analysis of the saturated water content value with the measurements of Pressure Plate Apparatuse results, named Yfc = -2.4742 + 0.6551 (x) and Yw = -16.949 + 0.557 (x). From the equation, then determined total available water based on the Karkanis Equation and the New Equation. The appropriateness test of the method of saturated water content using Graph 1: 1 was carried out on each total available water data (Karkanis equation and new equation) which results showed that the method was invalid to be applied to the study location (R2 = 0.0239). Key words: Total Available Water, Soil Texture, Pressure Plate Apparatus, Saturated Water Content ABSTRAK Penelitian mengenai penetapan kandungan air menggunakan metode pengukuran kandungan air jenuh telah dilakukan di Canada hasilnya sesuai untuk daerah tersebut. Namun metode tersebut perlu diuji untuk daerah tropika seperti di Jember. Penelitian ini dilakukan untuk mengetahui akurasi dan karakteristik persamaan empiris yang digunakan dalam penetapan total air tersedia dengan metode kandungan air jenuh pada beberapa kelas tekstur tanah. Contoh tanah terdiri atas zona Pegunungan Raung, Pegunungan Argopuro, dan Pegunungan Selatan yang diharapkan mewakili beberapa kelas tekstur. Persamaan empiris yang digunakan adalah Yfc = a + b(xfc), untuk kandungan air kapasitas lapang, Yw = a +b(xw), untuk kandungan air titik layu permanen. Persamaan empiris untuk total air teredia yaitu AT = Yfc - Yw. Hasil dari penelitian diperoleh Persamaan Baru dari hasil analisis regresi nilai kandungan air jenuh dengan hasil pengukuran Pressure Plate Apparatuse yaitu Yfc = -2,4742 + 0,6551 (x) dan Yw = -16,949 + 0,557 (x). Dari persamaan tersebut kemudian ditentukan total air tersedia berdasarkan Persamaan Karkanis dan Persamaan Baru. Uji kelayakan metode pengukuran kandungan air jenuh dengan menggunakan Grafik 1:1 dilakukan pada masing-masing data total air tersedia (Persamaan Karkanis dan Persamaan baru) yang hasilnya menunjukkan bahwa metode tersebut tidak valid/sahih untuk diterapkan pada lokasi penelitian (R2 = 0,0239). Kata Kunci : Total Air Tersedia, Tekstur tanah, Pressure Plate Apparatus, Kandungan Air Jenuh.